2014
DOI: 10.3389/fnagi.2014.00199
|View full text |Cite
|
Sign up to set email alerts
|

The ups and downs of global motion perception: a paradoxical advantage for smaller stimuli in the aging visual system

Abstract: Recent evidence suggests that normal aging is typically accompanied by impairment in the ability to perceive the global (overall) motion of visual objects in the world. The purpose of this study was to examine the interplay between age-related changes in the ability to perceive translational global motion (up vs. down) and important factors such as the spatial extent (size) over which movement occurs and how cluttered the moving elements are (density). We used random dot kinematograms (RDKs) and measured motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…In line with previous research, our findings confirm implication of orientation in the discharge of cells. [11,12], and showed that stimuli missing orientation; does not change significantly the responses of interneurons after the second stimulus. Discharge depends strongly of the influence of the second grating with an orientation.…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous research, our findings confirm implication of orientation in the discharge of cells. [11,12], and showed that stimuli missing orientation; does not change significantly the responses of interneurons after the second stimulus. Discharge depends strongly of the influence of the second grating with an orientation.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a direct experimental manipulation of attended-region size, one would simply be measuring participants' default or current attendedregion size and comparing the effect of an induced region size to this state. There indeed are demonstrable differences in default or preferred attended-region size across different groups, such as for people of different ethnicities, personality, and age groups (Elahipanah, Christensen, & Reingold, 2011;Greenwood & Parasuraman, 2004;Hutchinson, Ledgeway, & Allen, 2014;Kramer, Ellenberg, Leonard, & Share, 1996;McKone et al, 2010;Roalf, Lowery, & Turetsky, 2006;Wilson, Lowe, Ruppel, Pratt, & Ferber, 2016). Such default differences are not an issue here, because all of our key manipulations are manipulated within-subjects rather than between-subjects.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, speed discrimination (Genova & Bocheva, 2013;Norman, Ross, Hawkes, & Long, 2003) as well as motion direction discrimination (Ball & Sekuler, 1986;Bennett et al, 2007;Bocheva, Angelova, & Stefanova, 2013;Bogfjellmo et al, 2013) have been found to decline with increasing age. However, results seem to vary largely depending on stimulus parameters such motion direction (Ball & Sekuler, 1986;Pilz, Miller, & Agnew, 2017), stimulus size (Hutchinson, Ledgeway, & Allen, 2014), contrast (Allen et al, 2010), stimulus duration (Bennett et al, 2007;Conlon, Power, Hine, & Rahaley, 2017), or location (Wojciechowski et al, 1995). Indeed, the mechanisms that modulate age effects are often not well understood, but call for caution when trying to derive overall conclusions on functional changes.…”
Section: Global Motion Processingmentioning
confidence: 99%